Extended half‐life pegylated, full‐length recombinant factor VIII for prophylaxis in children with severe haemophilia A. Issue 2 (27th November 2016) - Mullins, E. S.; Stasyshyn, O.; Alvarez‐Román, M. T.; Osman, D.; Liesner, R.; Engl, W.; Sharkhawy, M.; Abbuehl, B. E.
Abstract : Introduction: Primary factor VIII (FVIII) prophylaxis is the optimal treatment in children with severe haemophilia A. They are expected to benefit from extended half‐life ( T 1/2 ) FVIII coverage by reduced infusion frequency while maintaining haemostatic efficacy. Aims: To determine immunogenicity, pharmacokinetics (PK), efficacy, safety and quality of life of prophylaxis with a polyethylene glycol (peg)‐ylated FVIII (BAX 855) based on full‐length recombinant FVIII (ADVATE) in paediatric previously treated patients (PTPs) with severe haemophilia A. Methods: PTPs <12 years without history of FVIII inhibitors received twice‐weekly infusions of 50 ± 10 IU kg −1 BAX 855 for ≥50 exposure days. Prophylactic dose increases to ≤80 IU kg −1 were allowed under predefined conditions. PK was evaluated after single infusions of 60 ± 5 IU kg −1 . Results: T 1/2 and mean residence time were extended 1.3‐ to 1.5‐fold compared to ADVATE ( n = 31), depending on the analysis used. The point estimate for the mean annualized bleeding rate in 66 subjects receiving a median of 1.9 weekly infusions of 51.3 IU kg −1 of BAX 855 each was 3.04 (median 2.0); 1.10 (median 0) for joint and 1.16 (median 0) for spontaneous bleeds. Overall, 38% of subjects had zero bleeds. No bleeds were severe. Haemostatic efficacy was rated excellent or good for 90% of bleeds; 91% were treated with one or two infusions. In 8/14 subjects all target joints resolved. No subject developed FVIII inhibitors or persistent binding antibodies that affected safety or efficacy. No adverse reactions occurred. Conclusion: Twice‐weekly prophylaxis with BAX 855 was safe and efficacious in paediatric PTPs with severe haemophilia A.